2020
DOI: 10.1111/tpj.14808
|View full text |Cite
|
Sign up to set email alerts
|

Exocyst mutants suppress pollen tube growth and cell wall structural defects of hydroxyproline O‐arabinosyltransferase mutants

Abstract: Summary HYDROXYPROLINE O ‐ARABINOSYLTRANSFERASEs (HPATs) initiate a post‐translational protein modification (Hyp‐Ara) found abundantly on cell wall structural proteins. In Arabidopsis thaliana , HPAT1 and HPAT3 are redundantly required for full pollen fertility. In addition to the lack of Hyp‐Ara in hpat1/3 pollen tubes (PTs), we also found broadly disrupted cell wall polymer distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 97 publications
6
55
0
Order By: Relevance
“…A recent genetic screen for suppressors of the hpat pollen phenotype identified mutants in the late stages of the secretory pathway, specifically in the vesicle-tethering exocyst complex. Beuder et al (2020) found that hpat pollen tubes had increased rates of HPATmodified protein secretion compared to WT pollen tubes and the rate of secretion was reduced in the suppressed line to near WT levels. This observation is consistent with a "toxic" effect of increased secretion of un-arabinosylated proteins.…”
Section: Hyp-o-glycosylated Proteins Contiguous Hyp-o-arabinosylationmentioning
confidence: 90%
See 3 more Smart Citations
“…A recent genetic screen for suppressors of the hpat pollen phenotype identified mutants in the late stages of the secretory pathway, specifically in the vesicle-tethering exocyst complex. Beuder et al (2020) found that hpat pollen tubes had increased rates of HPATmodified protein secretion compared to WT pollen tubes and the rate of secretion was reduced in the suppressed line to near WT levels. This observation is consistent with a "toxic" effect of increased secretion of un-arabinosylated proteins.…”
Section: Hyp-o-glycosylated Proteins Contiguous Hyp-o-arabinosylationmentioning
confidence: 90%
“…Somewhat surprisingly, the total loss of Hyp-arabinoslyation through mutations of all three Arabidopsis HPAT genes is not lethal and does not result in a severe vegetative phenotype ( MacAlister et al, 2016 ). The major phenotype of the triple mutants is a reduction in pollen fertility leading to reduced seed set ( Beuder et al, 2020 ). Similarly, HPAT activity is not essential in the moss Physcomitrella patens where knockout of both HPATs resulted in increased biomass due to enhanced elongation of tip-growing vegetative filament cells ( MacAlister et al, 2016 ).…”
Section: Discussion: Outstanding Questions and Future Research In mentioning
confidence: 99%
See 2 more Smart Citations
“…The two EXO70A isoforms, EXO70A1 ( Synek et al, 2006 ) and EXO70A2 ( Marković et al, 2020 ), seem to have a general housekeeping function during exocytosis in the sporophyte and the male gametophyte, respectively. Partially resembling the phenotypes of LOF mutants of core exocyst subunits, exo70A2 pollen grains germinate poorly and produce short, thick, slowly growing pollen tubes ( Beuder et al, 2020 ; Marković et al, 2020 ). In sharp contrast, LOF of Arabidopsis EXO70C2 results in stop-and-go growth dynamics where phases with abnormally high growth rates are interrupted by pollen tube tip bursts and recovery, ultimately resulting in pollen tube rupture ( Synek et al, 2017 ).…”
Section: Introductionmentioning
confidence: 96%